IFABP and TFF3 as predictors for intestinal health in the perioperative setting in children with congenital heart disease - Boerter, Nicolas; Freudenthal, Noa Judith; Bagci, Soyhan; Kratz, Tobias; Breuer, Johannes; Mueller, Nicole (Frontiers in Cardiovascular Medicine, 2025)
IntroductionChildren with congenital heart disease (CHD) undergoing cardiac surgery are at heightened risk of gastrointestinal complications due to imbalances in systemic and pulmonary blood flow, often resulting in impaired intestinal perfusion and mucosal injury. Intestinal biomarkers such as intestinal fatty acid binding protein (IFABP) and trefoil factor 3 (TFF3) indicate intestinal damage. This study investigates intestinal fatty acid binding protein (IFABP) and trefoil factor 3 (TFF3) as biomarkers for intestinal cell damage and their potential utility in predicting clinical outcomes particularly the progression of enteral feeding post-surgery.MethodsSerum and urine samples from 85 children with congenital heart defects were analyzed pre- and postoperatively at 6 time points focusing on IFABP and TFF3. IFABP and TFF3 levels were measured via ELISA and categorized into ordinal groups based on previous pediatric reference data and observed population distributions. A composite score (TI-score) combining urinary IFABP and serum TFF3 categories was created to improve predictive strength for outcome parameters. The primary outcome was time to full enteral nutrition; secondary outcomes included duration of invasive and non-invasive ventilation, vasoactive-inotropic score (VIS), and length of hospital stay.ResultsOf 85 analyzed patients, 73% showed elevated preoperative serum I-FABP levels (>336 pg/ml), with postoperative peaks at ICU admission and normalization within 60 h. The TI-score, combining both biomarkers, showed the strongest correlations with clinical outcomes such as duration of invasive ventilation (IV), duration of non-invasive ventilation (NIV), ventilation duration, time to full enteral nutrition and length of hospital stay (p < 0.01). TI-score at 12 h post-surgery independently predicted delayed enteral feeding and outperformed single biomarkers (AUC = 0.888; cut-off 6.5, sensitivity 84.4%, specificity 85%). Children with complex CHD or extracardiac shunts had significantly higher biomarker levels and TI-scores throughout the perioperative period.ConclusionIFABP and TFF3 are reliable biomarkers for assessing intestinal injury in children undergoing cardiac surgery. The TI-score provides enhanced prognostic value and may serve as a practical tool to guide clinical management and nutritional planning in this vulnerable population.